2021
DOI: 10.1177/24730114211060054
|View full text |Cite
|
Sign up to set email alerts
|

EMG Activity With Use of a Hands-Free Single Crutch vs a Knee Scooter

Abstract: Background: Foot and ankle injuries frequently require a period of nonweightbearing, resulting in muscle atrophy. Our previous study compared a hands-free single crutch (HFSC) to standard axillary crutches and found increased muscle recruitment and intensity while using the HFSC. Knee scooters are another commonly prescribed nonweightbearing device. The purpose of this study is to examine the electromyographic (EMG) differences between an HFSC and knee scooter, in conjunction with device preference and perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…A similar result was found when a subsequent study was performed this time comparing the muscle activity for the HFC with a knee scooter (Dewar et al, 2021). This study demonstrated a statistically significant increase in muscle recruitment while maintaining in phase muscle activation patterns consistent with normal walking when using the HFC compared to a knee scooter.…”
Section: Muscle Activity and Its Impact On Muscle Atrophysupporting
confidence: 83%
See 1 more Smart Citation
“…A similar result was found when a subsequent study was performed this time comparing the muscle activity for the HFC with a knee scooter (Dewar et al, 2021). This study demonstrated a statistically significant increase in muscle recruitment while maintaining in phase muscle activation patterns consistent with normal walking when using the HFC compared to a knee scooter.…”
Section: Muscle Activity and Its Impact On Muscle Atrophysupporting
confidence: 83%
“…Prior research shows that the HFC, crutches and knee scooters exhibit statistically significant differences in muscle activation for the lower extremities (Sanders et al, 2018;Dewar and Martin, 2020;Dewar et al, 2021;Clark et al, 2004;Seynnes et al, 2008). This is illustrated in Fig.…”
Section: Muscle Activity and Its Impact On Muscle Atrophymentioning
confidence: 85%
“…The effect of knee flexion in HFC was likely mitigated by its unique ambulation similar to walking gait, given that muscular activity is a major determinant of popliteal venous flow, and previously mentioned evidence demonstrates elevated surface electromyography when using HFC. 7 , 19 The use of HFC may be a better option than MKS in populations requiring foot/ankle unloading where venous pooling is of concern, such as those at risk for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…19 HFC use elevates muscle activation in the rectus femoris, vastus lateralis, and lateral gastrocnemius compared with AC and MKS. 7,8 Although not directly shown, these data may provide indirect evidence of the potential to mitigate atrophy and strength loss in specific muscle groups over the duration of an unloading period.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation